Dereverberation Sweet Spot Dilation with Combined Channel Equalization and Beamforming - Thomas, Mark; Gamper, Hannes; Tashev, Ivan (IEEE Intl. Conf. on Acoustics, Speech and Signal Processing (ICASSP), 2015)
Beamforming and channel equalizers can be formulated as optimal multichannel filter-and-sum operations with different objective criteria. It has been shown in previous studies that the combination of both concepts under a common framework can yield results that combine both the spatial robustness of beamforming and the dereverberation performance of channel equalization. This paper introduces an additional method for leveraging both approaches that exploits channel estimates in a wanted spatial location and derives robustness from knowledge of the array geometry alone. Experiments with an objective assessment of speech quality as a function of source perturbation reveal that the proposed technique can be viewed as a sweet spot dilator when compared with the MINT channel equalizer.